Genomic characterization of multidrug-resistant Salmonella Infantis isolated from chicken meat using Illumina and MinION sequencing in Korea - Tae-Min La; Sang Won Lee (Journal of Global Antimicrobial Resistance)
AIM: This study aims to investigate the genomic characteristics of multidrug-resistant (MDR) Salmonella Infantis isolated from chicken meat in Korea. BACKGROUND: The emergence of MDR Salmonella Infantis poses a significant threat to public health. Understanding the introduction and spread of these strains in Korea is crucial for developing effective control strategies.. METHODS: Salmonella Infantis isolates were collected from chicken meat samples in Korea. Antibiotic resistance tests were performed. Both Illumina and MinION sequencing technologies were used to perform a hybrid genome assembly. Comparative genomic analysis was conducted with other Salmonella Infantis strains from the NCBI database, including Korean isolates. Phylogenetic and BEAST analyses were performed to trace the origins and introduction timelines of the strains. RESULTS: All isolates (n=22) were MDR, resistant to 8 antibiotics. A closed circular genomes for all isolates were produced using hybrid genome assembly. Multiple antibiotic resistance genes, including aac(3)-IVa, aac(6’)-Iaa, ant(3’’)-Ia, aph(3’)-Ia, aph(4)-Ia, blaCTX-M-65, dfrA14, floR, sul1 and tetA, were detected and mostly located on pESI-like plasmid. Phylogenetic analysis showed distinct clustering patterns of Korean isolates, suggesting multiple introductions into Korea. BEAST analysis confirmed independent introductions over various periods from different countries. CONCLUSIONS: The findings highlight the critical need for ongoing genomic surveillance and comprehensive analysis of MDR Salmonella Infantis. The distinct phylogenetic clusters and BEAST analysis suggest multiple introductions from international sources. It is essential to implement stringent biosecurity measures and develop targeted strategies to mitigate the spread of MDR Salmonella Infantis, ensuring public health safety.